2015
DOI: 10.11610/isij.3301
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Security and Some Implemental Limits

Abstract: The changing security environment has led to the development of comprehensive security approaches, strategies and policies. The 'Holistic approach' has become an academic and practical mantra. This paper argues, however, that comprehensive security approaches face serious obstacles to their practical implementation. The critical evaluation of several examples confirms that the implementation phase is a weakness of comprehensive approaches and that a truly comprehensive and holistic approach seems to be beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The critical evaluation of several examples confirmed that the implementation phase is a weakness of comprehensive approaches and that a truly comprehensive and holistic approach seems to be beyond the implemental capacities of our security systems. 23 Such conclusions on the difficulties on the one hand and the need for interorganizational cooperation on the other represent a huge motivation for further work in this field and also a motivation for working on this special journal issue.…”
Section: Interorganizational Approach In Crisis Management and Counter-terrorism -The Guest Editor's Experiencementioning
confidence: 99%
“…The critical evaluation of several examples confirmed that the implementation phase is a weakness of comprehensive approaches and that a truly comprehensive and holistic approach seems to be beyond the implemental capacities of our security systems. 23 Such conclusions on the difficulties on the one hand and the need for interorganizational cooperation on the other represent a huge motivation for further work in this field and also a motivation for working on this special journal issue.…”
Section: Interorganizational Approach In Crisis Management and Counter-terrorism -The Guest Editor's Experiencementioning
confidence: 99%